2022
DOI: 10.3390/jpm12020294
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cardiac Magnetic Resonance-Assessed Replacement and Interstitial Fibrosis and Ventricular Arrhythmias in Hypertrophic Cardiomyopathy

Abstract: Non-sustained ventricular tachycardia (nsVT) creates the electrical basis for sudden cardiac death (SCD) in hypertrophic cardiomyopathy (HCM). We aimed to evaluate the relationship between interstitial fibrosis on cardiac magnetic resonance (CMR) and nsVT in HCM. A total of 50 HCM patients underwent CMR with a 3 T scanner to determine the presence of replacement fibrosis expressed by late gadolinium enhancement (LGE), and interstitial fibrosis expressed by native T₁, post-contrast T₁, and extracellular volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…In the sub-analysis involving only patients with LGE presence, troponin levels presented a tendency to predict higher LGE extent in the univariable analysis, and only EF and VT were associated with LGE extent. It is worth remarking that this observed association could well be interpreted in the following way: LGE extent is a VT predictor (which we and others have shown previously), not the other way round [9,11]. Several authors have also observed higher levels of TnT in HCM patients with LGE presence [12,13], and yet in other studies, there have been associations reported between TnT levels and LGE mass or extent [14,15].…”
Section: Biomarkers and Replacement Fibrosissupporting
confidence: 69%
See 1 more Smart Citation
“…In the sub-analysis involving only patients with LGE presence, troponin levels presented a tendency to predict higher LGE extent in the univariable analysis, and only EF and VT were associated with LGE extent. It is worth remarking that this observed association could well be interpreted in the following way: LGE extent is a VT predictor (which we and others have shown previously), not the other way round [9,11]. Several authors have also observed higher levels of TnT in HCM patients with LGE presence [12,13], and yet in other studies, there have been associations reported between TnT levels and LGE mass or extent [14,15].…”
Section: Biomarkers and Replacement Fibrosissupporting
confidence: 69%
“…CMR imaging with cine CMR, native and post-contrast T1 mapping, and LGE imaging was performed on a 3T CMR scanner (Magnetom Skyra, Siemens, Erlangen, Germany) according to local imaging protocols, as previously described [9]. The analyses were conducted with Syngo.…”
Section: Cardiac Magnetic Resonance (Cmr)mentioning
confidence: 99%
“…These patients often neglect appropriate treatment due to the satisfactory EF value. However, previous studies have reported that some patients with HCM with preserved EF have adverse outcomes, such as cardiac insufficiency, the requirement of implantable defibrillator surgery, and sudden cardiac death (10,11). Therefore, identifying impaired cardiac function in patients with HCM with preserved EF is a key clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…Aleksandra Karabinowska-Małocha and colleagues studied the relationships between replacement by means of late gadolinium enhancement (LGE) and interstitial (via T1-mapping) fibrosis and arrhythmic burden in HCM. The authors concluded that only the quantitative assessment of replacement fibrosis by LGE extent determines the occurrence of ventricular arrythmias in HCM, whereas the role of interstitial fibrosis in this context remains unclear [ 5 ]. Morbidity and mortality (5-year mortality of 20%) is high in DCM patients, yet there is lack of reliable tools to precisely calculate the risk.…”
mentioning
confidence: 99%